STORIE MANDALICHE (2000-2004): Iper-racconti di trasformazione (Connessioni remote. Artivismo_Teatro_Tecnologia, 2020)
Storia Mandaliche is based on hypertext written by Andrea Balzola with seven stories that are interlinked; every story touches the other characters in different moments and ways; it’s the first Italian theatrical hypertext, created in the first version, more than ten years ago. We have calculated that 5.040 stories are possible in a new combinatorial narration, no longer linear but simultaneous and labyrinthic. In the vertical sense you can see the chronological story of the seven characters but there are several links that join one to another in a horizontal sense that produce a sense of infinity. In the first version of the show the choice of the path, the choice of the character’s point of view was given to the audience and the interactivity system was Mandala System created in the 80’s by the Canadian group Vivid; it’s one of the first experiences of non immersive virtual reality, an archaic motion capture system which allows the digitalizing of objects shot by a video camera in real time such as a lumakee, and the objects come onto the laptop screen becoming interactive, generating sounds, and graphic signs. The digital story teller was Giacomo Verde. Here is one of the first exhibition: